A phase 1 study of eribulin mesylate (E7389), a novel microtubule‐targeting chemotherapeutic agent, in children with refractory or recurrent solid tumors: A Children's Oncology Group Phase 1 Consortium study (ADVL1314). Issue 8 (2nd May 2018) - Schafer, Eric S.; Rau, Rachel E.; Berg, Stacey; Liu, Xiaowei; Minard, Charles G.; D'Adamo, David; Scott, Rachael; Reyderman, Larisa; Martinez, Gresel; Devarajan, Sandhya; Reid, Joel M.; Fox, Elizabeth; et al.
Abstract: Background: Eribulin mesylate is a novel anticancer agent that inhibits microtubule growth, without effects on shortening, and promotes nonproductive tubulin aggregate formation. We performed a phase 1 trial to determine the dose‐limiting toxicities (DLTs), maximum tolerated or recommended phase 2 dose (MTD/RP2D), and pharmacokinetics (PK) of eribulin in children with refractory or recurrent solid (excluding central nervous system) tumors. Methods: Eribulin was administered intravenously on days 1 and 8 in 21‐day cycles. Three dose levels (1.1, 1.4, and 1.8 mg/m 2 /dose) were evaluated using the rolling six design with additional patients enrolled into a PK expansion cohort at the MTD. PK samples were obtained following the day 1, cycle 1 dose. Results: Twenty‐three patients, ages 3–17 (median 14) years were enrolled; 20 were evaluable for toxicity. DLTs occurred in 0/6 and 1/6 subjects at the 1.1 and 1.4 mg/m 2 /dose, respectively. One subject at the 1.4 mg/m 2 /dose had grade 4 neutropenia and grade 3 fatigue. At the 1.8 mg/m 2 /dose, 2/5 subjects experienced dose‐limiting (grade 4) neutropenia. Grade 3/4 non‐DLTs included lymphopenia and hypokalemia, while low‐grade toxicities included anorexia and nausea. No episodes of grade > 2 corrected QT interval prolongation or peripheral neuropathy were reported. Eribulin pharmacokinetic parameters were highly variable; the median elimination half‐life was 39.6 (range 24.2–96.4) hr. A partial response was observed in one patient (Ewing sarcoma). Conclusions: Eribulin was well tolerated in children with refractory or recurrent solid tumors with neutropenia identified as the primary DLT. The RP2D of eribulin is 1.4 mg/m 2 /dose on days 1 and 8 of a 21‐day cycle.